The adoption of looked after maltreated children in England: challenges, opportunities and outcomes - Selwyn, J (Association of Children's Welfare Agencies, 2017)
In England about 72,670 children were in care at 31st March 2017 (Department for Education, 2017). Unlike Australia, few of these children were placed with kinship carers: only 11% were placed with an approved foster carer who was a relative or friend of the family. More children are living with kinship carers under a special guardianship order but once the order is made children are no longer deemed to be in care. Consequently, most children in care (approx. 64%) are living with unrelated foster carers. Foster carers are professionals who are approved and registered with an agency and who receive a fee on the basis of being self-employed.